Gruppenaufnahme - Marc Darchinger
Mitglieder SPD-Parteivorstand Rudolf Scharping, Regine Hildebrandt, Herta Däubler-Gmelin, Wolfgang Thierse, Wolfgang Clement, Hans Eichel, Christine Bergmann, Heide Simonis, Franz Müntefering; Bundeskanzler Gerhard Schröder;